Simulasi Pengamanan Virtual Server Menggunakan Dionaea Honeypot Dan Tunneling Sebagai Proses Pengamanan Komunikasi Data - Nauval Alfarizi; Tengku Mohd Diansyah; Risko Liza (SNASTIKOM, 2022)
Cybercrime is carried out to obtain information, where the information obtained is used as a source of data in carrying out an attack. Attacks generally lead to various scopes ranging from physical servers to virtual servers. This research was conducted by the author to be able to carry out the implementation process based on qualitative development of existing technology, namely the design of a virtual server system using Dionaea honeypot and PPTP tunneling in carrying out a form of security for data communication that can cover vulnerabilities to a device on a virtual server. The results of the research that the author conducted showed that there was a difference in each attack test. When an attack attempt is carried out into each port that is not configured on the main service on the virtual server, the results of the attack are that it can detect intruders and vice versa